Iowa RBA, February 24, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for February 24, 1997. Highlights of the update include the continued presence of Great Gray Owls and a Ferruginous Hawk as well as sightings of a Prairie Falcon and a Townsend's Solitaire. Also included are handwritten notes for the next week's update with sightings of a Northern Shrike and six Red Crossbills. Epson - sheet feed/flatbed